Immunodominant Major Outer Membrane Proteins of Ehrlichia chaffeensis Are Encoded by a Polymorphic Multigene Family - Ohashi, Norio (American Society for Microbiology, 1998)
Several immunodominant major proteins ranging from 23 to 30 kDa were identified in the outer membrane fractions of Ehrlichia chaffeensis and Ehrlichia canis. The N-terminal amino acid sequence of a 28-kDa protein of E. chaffeensis (one of the major proteins) was determined. The gene (p28), almost full length, encoding the 28-kDa protein was cloned by PCR with primers designed based on the N-terminal sequence of the E. chaffeensis 28-kDa protein and the consensus sequence between the C termini of the Cowdria ruminantium MAP-1 and Anaplasma marginale MSP-4 proteins. The p28 gene was overexpressed, and antibody to the recombinant protein was raised in a rabbit. The antibody and serum from a patient infected with E. chaffeensis reacted with the recombinant protein, three proteins (29, 28, and 25 kDa) of E. chaffeensis, and a 30-kDa protein of E. canis. Immunoelectron microscopy with the rabbit antibody revealed that the antigenic epitope of the 28-kDa protein was exposed on the surface of E. chaffeensis. Southern blot analysis with a (32)P-labeled p28 gene probe revealed multiple copies of genes homologous to p28 in the E. chaffeensis genome. Six copies of the p28 gene were cloned and sequenced from the genomic DNA by using the same probe. The open reading frames of these gene copies were tandemly arranged with intergenic spaces. They were nonidentical genes and contained a semivariable region and three hypervariable regions in the predicted protein molecules. One of the gene copies encoded a protein with an internal amino acid sequence identical to the chemically determined N-terminal amino acid sequence of a 23-kDa protein of E. chaffeensis. Immunization with the recombinant P28 protein protected mice from infection with E. chaffeensis. These findings suggest that the 30-kDa-range proteins of E. chaffeensis represent a family of antigenically related homologous proteins encoded by a single gene family.